The influence of Bruno Schütt (1876–1956) on Albanian floristic research - Barina, Zoltán; Pifkó, Dániel; Somogyi, Gabriella (Phytotaxa, 2016)
A revision of Bruno Schütt’s herbarium is here discussed, and a reconstruction of the routes of his collecting trips in Albania between 1927 and 1939 is presented. Schütt’s herbarium was not available to the public until recently. However, a manuscript, compiled by him, including the records of collected taxa, was used to outline their distribution of taxa by countries in Flora Europaea and subsequent works. Due to the few original floristic records from Albania, the presence of some taxa in Albania is partly or completely based on Schütt’s material. Some of his records are questionable as there is no voucher specimen for them, or they were originally misidentified. Based on our results, Arabis ciliata, Campanula macrostachya, Carduus carduelis, Crepis froelichiana subsp. dinarica, Crepis pantocsekii, Geranium divaricatum, Orobanche artemisiae-campestris and Potentilla patula were erroneously reported from Albania; and Alchemilla connivens, Knautia dipsacifolia, Linum perenne subsp. alpinum, Soldanella hungarica and Waldsteinia geoides are newly reported. Adonis vernalis is also questionably reported here for the Albanian flora based on Schütt’s material.